MENUMBUH-KEMBANGKAN KARAKTER KONSELOR PROFESIONAL : MENUJU TRADISI NILAI UNTUK DINILAI - Farida Harahap (Paradigma, 2006)
According to the National Education System Law, universities as one of educational institutions have the mandate to shape the personal characters of their students. A personal character constitutes the process and product of the period when students are learning in an educational institution. Compared to private educational institutions, state educational institutions seem to be ashamed or afraid to explicitly publish the self-image of their “outcomes” under the brand names that they bear. BK FIP UNY is a brand name in the eyes of the community. So far, as educational institutition has not yet clearly depict the practical capability and personal characters of human resources who become its civitas academica as a specific characteristic “shaped” by BK FIP UNY. Character shaping is an inheritance of value tradition from one generation to the next, as a culture in academic atmosphere. The values to be made as tradition are universal principles which can cover its vision in the future. Inheriting those values cannot be left to the students alone, but it must be started from the top executive of the institution. In the process, it needs commitment of all involved parts, a sustainable system of inheriting the values, and high consistency and loyalty to cultivate the value tradition. As a result, this value tradition will be reflected in daily academic atmosphere and in a comprehensive personal character of all civitas academica of BK FIP UNY and turn to be a self-image with which we can be proud of if judged by the community.Key words : value tradition, brand image